Androgen deprivation therapy and radiotherapy in intermediate-risk prostate cancer: A systematic review and meta-analysis - Chen, Jiuzhou; Yuan, Yan; Fang, Miao; Zhu, Youqi; Sun, Xueqing; Lou, Yufei; Xin, Yong; Zhou, Fengjuan (Frontiers in Endocrinology, 2023)
Objectives: Androgen deprivation therapycombining with radiotherapy for intermediate-risk prostate cancer is still a matter of debate. We conducted a meta-analysis to evaluate the necessity of androgen deprivation therapy combined with radiotherapy for intermediate-risk prostate cancer patients. Methods: A comprehensive literature search of articles was performed in PubMed, Embase, Cochrane library, Web of Science, Chinese National Knowledge Infrastructure, Chinese Biological Medicine, Wanfang, and VIP Databases published between February 1988 and April 2022. Studies comparing the survival of patients diagnosed with intermediate-risk prostate cancer who were treated with androgen deprivation therapy combined with radiotherapy or radiotherapy alone were included. Data were extracted and analyzed with the RevMan software (version 5.3) and the Stata software (version 17). Results: Six randomized controlled trials and nine retrospective studies, including 6853 patients (2948 in androgen derivation therapy combined with radiotherapy group and 3905 in radiotherapy alone group) were enrolled. Androgen deprivation therapy combined with radiotherapy did not provide an overall survival (HR 1.12, 95% CI 1.01-1.12, p=0.04) or biochemical recurrence-free survival (HR 1.23, 95% CI 1.09-1.39, P=0.001) advantage to intermediate-risk prostate cancer patients. Conclusion: Androgen deprivation therapy combined with radiotherapy did not show some advantages in terms of overall survival and biochemical recurrence-free survival and radiotherapy alone may be the effective therapy for intermediate-risk prostate cancer patients. Systematic review registration: https://inplasy.com/inplasy-2022-8-0095/.